The Influence of Creativity on the Entrepreneurial Attitudes of Economic Education Students in Pekanbaru - Donal; Ryantama Isjoni, M Yogi; Suri, Intan; Apriani, Aulia; Sintia, Apen (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
The high unemployment rate among university graduates demonstrates the need to enhance entrepreneurial competencies. Although entrepreneurship programs have been provided, many students struggle to apply the knowledge. Creativity is believed to be a key factor that can encourage entrepreneurial attitudes through the creation of innovative ideas. This study aims to determine the effect of creativity on the entrepreneurial attitudes of Economics Education students in Pekanbaru. The study employed a quantitative approach with a sample of 170 students from the University of Riau and Sultan Syarif Kasim State Islamic University, selected through a purposive random sampling technique with the Slovin formula. Data collection was carried out using a Likert scale questionnaire, and data analysis was conducted using simple linear regression. Pre-requisite tests showed that the data were normally and linearly distributed. The results implied that creativity had a positive and significant effect on entrepreneurial attitudes. Thus, the higher the students' creativity, the more positive their attitudes towards entrepreneurship.